The Students’ Ability in Expressing Gratitudeand Appreciation by Using Think Pair Share Strategy at Sixth Grade Students of SD Yabes School Medan - Saragih, Marice; Tampubolon, Jonris (Journal of Applied Linguistics, 2021)
The objectives of this research are to find out the students ability in expressing gratitude and appreciation by using Think-Pair-Share Strategy and to find out the achievement levels of the students ability in expressing gratitude and appreciation by using think pair share strategy at the sixth grade students of SD Yabes School. The good teacher is able to find the good strategy in the teaching and learning process so that the students will interest to study English. One of strategy used in teaching speaking ability in express gratitude and appreciation is Think-Pair-Share Strategy. The population of this study was all of the sixth grade students of SD Yabes School which consist of 30 students, all the population used as the sample so that the sample consist of 30 students.This study use quantitative research using an experimental design and control design, the examiner intentionally revised appearance of the difference and then it was examined how the result was. This research required two groups of student namely experimental group and control group. experimental group was treated with Think-Pair-Share Strategy during speaking. where as control group was treated without Think-Pair-Share. From the total score pre test of the experimental class (1.600) and the total score pre test of the control class (1.360) can be concluded that the achievement of both group was the same. After getting the treatment (Thik-Pair-Share), the total score post-test of the experimental (2.337) was higher than the total score post-test of the control class (1.686) which did not get the treatment. It can be said that teaching Think-Pair-Share gave positive effect on the students, speaking achievement in expressing gratitude and appreciation Key Words : Gratitude and Appreciation, Think-Pair-Share Strategy